Analysis of Factors Affecting the Coordination Function in the Implementation of Infection Prevention and Control (IPC) Programs by Infection Prevention Control Link Nurses (IPCLN) at Hospital X Jakarta - Simin, Desmalia Maulana; Pamungkas, Rian Adi; Johanes, Johanes; Novita, Dian (Universitas Malahayati, 2025)
ABSTRACT Based on report data from the Infection Prevention and Control Committee of X Hospital, the incidence of Health Care Associated Infection, namely Surgical Area Infection (SSI), increased in 2022 - 2024. The purpose of this study is to analyse the factors that influence the coordination function of the implementation of the IOP programme at IPCLN in Hospital Jakarta in 2024. This study used an analytical survey research design using a cross sectional approach, the population in this study were all IPCLNs at Hospital X Jakarta in 2024 amounting to 57 people and the sample used a total population which means that all IPCLNs at Hospital X Jakarta in 2024 amounting to 57 people were taken as research subjects. Univariate data analysis was carried out using the three box method, partial bivariate analysis using simple linear regression and simultaneous multivariate analysis using multiple linear regression using the help of the SPSS programme. The results of partial bivariate analysis obtained there is an influence of competence (p value = 0.000 < 0.05), there is an influence of supervision (p value = 0.000 < 0.05), there is an influence of the reward system (p value = 0.000 < 0.05) and there is an influence of awareness on the coordination function of the implementation of the PPI programme at IPCLN (p value = 0.000 < 0.05). The results of multivariate analysis simultaneously obtained there is an effect of competence, supervision, reward system and awareness simultaneously on the coordination function of the implementation of the IPI programme at IPCLN (p value = 0.000 < 0.05) and the most dominant supervision variable affects the coordination function (p value = 0.000 < 0.05). It is expected that IPCLN implementing nurses: improve skills in implementing PPI, take corrective action if the target results of PPI implementation are not in accordance with predetermined targets, give awards to nurses in each unit who excel in implementing PPI based on performance monitoring, openly accept other people's criticism in carrying out IPCLN functions in the field of PPI and try to comply with all applicable rules in carrying out implementation as IPCLN in the field of PPI. Keywords: Competence, Supervision, Reward, Awareness, Coordination Function